1997
DOI: 10.1159/000196704
|View full text |Cite
|
Sign up to set email alerts
|

A Free Radical Scavenger (Lazaroid U75412E) Attenuates Tumor Necrosis Factor-Alpha Generation in a Rabbit Model of Smoke-Induced Lung Injury

Abstract: The lazaroid (21-aminosteroid) analogue U75412E was evaluated in rabbits exposed to diesel fuel-polycarbonate plastic smoke. Inhalation of a total of 4.6 mg U75412E aerosolized at a rate of 1.53 mg/min for 3 min before or after smoke significantly prevented or limited the extent of alveolar hypoventilation, interstitial edema, and tumor necrosis factor-α (TNF-α) by pulmonary alveolar macrophages (PAM) ex vivo observed at 2 h. The smoke-induced changes in wet lung/body weight ratios and the production of supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…This finding is consistent with results of previous work that utilized the pretreatment of smoke-exposed animals with U75412E (34,35). Lazaroid treatment prevented smoke-induced changes in blood Pa02, PaC02, pH, and COHb°lo.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with results of previous work that utilized the pretreatment of smoke-exposed animals with U75412E (34,35). Lazaroid treatment prevented smoke-induced changes in blood Pa02, PaC02, pH, and COHb°lo.…”
Section: Discussionsupporting
confidence: 92%
“…In vivo efficacy of lazaroids has been documented in animal models of lung injuries induced by endotoxins (17), silica (16), oxidants (11), phorbol esters (22), and bleomycin (21). In an established rabbit model, lazaroid U75412E attenuated chemical mediators after smoke insult (34,35). These studies suggest that lazaroids may exert their protective action not only by a direct antioxidant activity (1,19,29,30) and inhibition of lipid peroxidation (17) but also by suppressing the expression and/or release of cytokines (28), such as interleukin-8 (22) and tumor necrosis factor-a (TNF-a) (35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that exposure to cotton smoke enhanced basal production of superoxide by rabbit alveolar macrophages within 70 min postinjury [3]. Wang et al [25] reported that inhalation of smoke generated by combustion of diesel fuel and polycarbonate plastic shavings increased basal production of superoxide by rabbit alveolar macrophages by 2 h postexposure but did not alter zymosan-induced superoxide generation. In contrast, Witten et al [27] found that inhalation of diesel fuel-polycarbonate plastic smoke inhibited PMA-induced superoxide production in rabbit alveolar macrophages at 40 min postexposure.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism(s) underlying the inhibitory effect of NIM on TNF-α is still unknown. In previous studies, it was demonstrated that different antioxidants are able to reduce TNF-α production [41, 42], and it should be mentioned that NIM exhibits antioxidant activity by reducing the generation of superoxide anions and scavenging hypochlorous acid [43]. However, relying on the data regarding the effects of other COX inhibitors on the NF-ĸB pathway [37, 39], there was a basis to hypothesize that NIM might also inhibit TNF-α in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%